PENDIDIKAN KESETARAAN GENDER DALAM ISLAM PERSPEKTIF KH HUSEIN MUHAMMAD - M. Amin Selamet; Wiwin Fachrudin Yusuf (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
Education is a very strategic medium for socialization as well as transforming the values and norms that apply in people's lives, both social, cultural and religious. The educational process is actually relatively easy to organize, for example within the family sphere, where parents become educators for their children. This research focuses on exploring how the concept of gender equality education in Islam is a KH perspective. Husein Muhammad and how to provide gender equality education in Islam KH Perspective. Hussein Muhammad. This research is a library research ( Library Research), by discussing how the concept of gender equality education in Islam is from the perspective of KH. Hussein Muhammad. Data collection is carried out by reading, recording, studying and analyzing books, scientific journals, scientific research and other scientific writings. Data analysis is carried out by interpreting or interpreting the data obtained (Descriptive Analytics). In checking the validity of the data findings, researchers use the triangulation method. The results of this study show that, 1) According to KH Hussein Muhammad, Islamic education must use an emancipatory paradigm so that the educational process is more democratic and egalitarian. Islamic education must use the feminist paradigm to build awareness of oppression. People's education as an open educational process and providing equal opportunities for the community must provide a meter that contains the values of gender equality. The development of a gender equality perspective towards pesantren families is very necessary to be carried out so that the learning process and learning curriculum contain the values of gender equality. 2) KH Husein Muhammad organized gender equality education through non-formal education channels, namely in the organizations he founded and cared for, but over time he also organized formal gender equality education, namely through the Fahmina Institute of Islamic Studies (ISIF).